MRI does not effectively diagnose ulnar-sided wrist pain in elite tennis players. Issue 6 (June 2020) - Reid, Machar; Wood, Timothy; Montgomery, Anne-Marie; Botterill, Elissa; Kovalchik, Stephanie; Omizzolo, Melanie; Malara, Frank; Rotstein, Andrew; Hoy, Gregory
Abstract: Objectives: Ulnar-sided injuries of the non-dominant wrist are common in elite tennis players using a double-handed backhand technique. This study investigated the radiological changes of the non-dominant wrist in elite symptomatic and asymptomatic players using this technique as well as healthy controls. We compared clinical findings to radiological abnormalities. Design: Cross-sectional design with blinded radiological assessment, and contemporaneous clinical assessment of symptomatic players. Methods: Magnetic resonance images (MRI) of wrists related to non-dominant ulnar-sided pain, were taken in 14 symptomatic tennis players, 14 asymptomatic tennis players, and 12 healthy controls which were then independently reviewed for abnormalities by blinded radiologists. Total abnormalities and global between-group differences in the triangular fibrocartilage complex (TFC), ulnar collateral ligament (UCL), extensor carpi ulnaris (ECU) and supporting structures, osseous-articular lesions and ganglia were assessed. These were then compared to clinical examinations of the symptomatic players to assess agreement. Results: Symptomatic players reported a mean 3.64 abnormalities, being exactly 1 abnormality greater than asymptomatic players (2.64) and controls (2.50), suggesting similar asymptomatic lesions in all three groups. Players with pain reported significantly more osseous-articular lesions, ECU tendon and dorsal radio-ulnar ligament abnormalities, while changes to the UCL may reflect an isolated problem in specific wrists. There were no between-group differences in the presence of ganglia, most TFC structures nor ECU subsheath tear and subluxation. Conclusions: Clinicians should carefully consider radiological changes alongside their clinical diagnosis of non-dominant wrist pain in tennis players due to possible tennis-related changes and/or asymptomatic findings.